2017
DOI: 10.1103/physrevfluids.2.083901
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic disturbances and their consequences in rotating channel flow transition

Abstract: It is now established that subcritical mechanisms play a crucial role in the transition to turbulence of non-rotating plane shear flows. The role of these mechanisms in rotating channel flow is examined here in the linear and nonlinear stages. Distinct patterns of behaviour are found: the transient growth leading to nonlinearity at low rotation rates Ro, a highly chaotic intermediate Ro regime, a localised weak chaos at higher Ro, and complete stabilization of transient disturbances at very high Ro. At very lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This growth can trigger nonlinearities, and lead to transition to turbulence, as has been shown for PPF and PCF [29,30]. In RPPF, Jose et al [31] showed that even when the flow is linearly unstable, there exist regimes where perturbation energy can be enhanced significantly by transient algebraic growth. Besides this well-known property of non-normality, we show here that non-normality in a particular flow system can be the reason for a large decrease in the critical Reynolds number of a closely related flow.…”
Section: Introductionmentioning
confidence: 90%
“…This growth can trigger nonlinearities, and lead to transition to turbulence, as has been shown for PPF and PCF [29,30]. In RPPF, Jose et al [31] showed that even when the flow is linearly unstable, there exist regimes where perturbation energy can be enhanced significantly by transient algebraic growth. Besides this well-known property of non-normality, we show here that non-normality in a particular flow system can be the reason for a large decrease in the critical Reynolds number of a closely related flow.…”
Section: Introductionmentioning
confidence: 90%
“…The transient energy growth was argued to be responsible for transition from laminar flow at subcritical values of the Reynolds number (Brandt 2014). In the unstable regime, it was shown that the non-modal effects can enhance perturbation energy significantly before modal behavior dominates, and therefore can be considered important for studying transition scenarios (e.g., Lucas et al, 2015, Jose et al, 2017.…”
Section: Introductionmentioning
confidence: 99%